Exploring the environmental awareness: Knowledge, attitudes, and behaviors in Indonesia's academic community - Hendra Michael Aquan; Luisa Diana Handoyo; Antonius Tri Priantoro (University of Muhammadiyah Malang, 2025)
This study examines environmental awareness at a university in Indonesia, focusing on knowledge, attitudes, and behaviors in seven environmental areas: climate, water, food, energy, natural resources, biodiversity, and waste. A total of 442 respondents (380 students, 42 lecturers, 20 educational staff) were surveyed using a Likert scale questionnaire. The data obtained was then analyzed quantitatively using ANOVA. The mean scores for the knowledge dimension across the three respondent groups were: lecturers (4.60), educational staff (4.23), and students (4.32). The mean scores for the attitude category were: lecturers (4.44), while students and educational staff had the same mean score of 4.12. In the environmentally friendly behavior category, the mean scores were: lecturers (4.18), students (3.73), and educational staff (3.95). Statistical analysis results show that the lecturer group differs significantly compared to students and educational staff across all three dimensions. These findings indicate that lecturers consistently demonstrate higher environmental awareness in all categories. There were no significant differences between student and educational staff groups. From these findings, there is a need to strengthen environmental awareness through knowledge, attitudes, and behaviors among student and educational staff groups. Strengthening awareness among students can be done through integration of environment-related courses and extracurricular activities, while for educational staff it can be done through regular training and workshops in environmental management.